Seasonal Variation in the Reproduction of Anodonta woodiana in The Lahumbuti River, Konawe Regency, Southeast Sulawesi - Bahtiar Bahtiar; Muh. Fajar Purnama; Meriyani Syalam; Marifatul Munawarah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mussel mussels are invasive shellfish whose reproductive potential in the Lahumbuti River is unknown. This study aims to determine the seasonal variations in the reproduction of mussel shells in the Lahumbuti River, Southeast Sulawesi. This research was carried out in the Lahumbuti River Konawe, Southeast Sulawesi in 2 periods, namely: May-October 2021 and February-June 2022. The mussels were collected manually using a hand scoop. Furthermore, the shells are washed from dirt/soil attached to the shell. The length and weight of the mussels (total weight and meat weight) were measured using a caliper and a digital scale with an accuracy of 0.5 mm and 0.01 g, respectively. TKG was observed microscopically by using a gonad microscope. Fecundity was calculated by the number of type D spats in the mussel gill sieves. The results showed that male and female mussels were in developmental phases (TKG I, II and III), gonadal maturity (TKG IV) and spawning (TKG V) were found throughout the season. The actual IKG values ​​did not differ based on the time of observation, although there was a tendency for the IKG values ​​to be found to be higher in February-April. Fecundity of mussel mussels ranged from 16317-58429. The size at first maturity of male and female mussel mussels occurred at 3.9 cm and 4.7 cm, respectively.